Democracy promotion in the age of social media: risks and opportunities - Anita Breuer (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The potential that Social Digital Media (SDM) have to support and promote democracy is attracting growing interest from researchers and policy-makers. However, the debate on this issue is controversial. The prominent role played by SDM in the popular uprisingsacross North Africa and the Middle East has led to the coining of the catchphrase “Social Media Revolution”. Yet critics argue that some Western policy-makers may be hamstrung by a cyber-utopian view that regards the Internet as inherently pro-democratic. The undifferentiated call for “Internet freedom” that results from such cyber-utopism is a dangerous one. Rather than that, policy makers should start out by asking how SDM can be used to sideline existing policies on democracy assistance in a given country and let the answer to that question shape their strategic choices. Any serious debate on the promise of SDM to aid democracy promotion must consider that different types of SDM vary in their specific characteristics and that such variation translates into different opportunities and risks depending on the political context in which they are employed. In closed societies, where the dissemination of suppressed information is critical for the creation of a rhetorical space beyond the control of the state, efforts should concentrate on circumventing censorship and facilitating access to types of SDM capable of generating high-quality content, especially blogs and collaborative projects . Where the mobilisation of civil society is needed to challenge irresponsive and reform-adverse governments, social networks and content communities should be the focus of attention. However, digital activists would have to be trained in the safe use of such platforms to evade government surveillance and persecution. Experience shows that social media assistance stands a better chance of succeeding if it adopts a country- and issue-oriented approach. Non-state donors with close ties to local actors, such as political foundations, church organizations and domestic non-governmental organizations (NGOs) in developing countries, are more likely than state-owned donor agencies to develop programmes that relate to existing networking structures and to enjoy credibility and legitimacy in the communities of the recipient countries. Direct government action to promote Internet freedom should concentrate on domestic tasks. Many of the tools used by authoritarian governments to monitor and silence digital dissent are engineered and distributed by US and European companies. Hence, export restrictions on censoring and filtering software should not be viewed as avoidable obstacles, but rather as a fundamental investment in democracy promotion. Furthermore, the development of proper policy incentives will be essential if companies are to be convinced to consider user protection as a central part of their business mission. It is not a given that SDM service providers should expand business at the cost of their users' privacy.
Keywords: 330